2022
DOI: 10.1177/23998083221084990
|View full text |Cite
|
Sign up to set email alerts
|

Generating megacity-scale building height maps without DGNSS surveyed GCPs: An open-source approach

Abstract: This paper describes an open-source method for generating megacity-scale building height maps without proprietary software or Differential Global Navigation Satellite System surveyed ground control points (GCPs). We use the open-source Satellite Stereo Pipeline (S2P) software along with four scenes of 2.5m resolution Cartosat-1 data for Bengaluru to demonstrate this. Digital Surface Models (DSMs) of 5 m resolution are generated using S2P, and terrain removal is achieved using 30m SRTM data resampled to 5m. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…In the other cases, there was a difference of 1 floor. This is acceptable and comparable with other open-source tools that achieve an error of 1 floor in building heights, which is sufficient for most city-scale analysis [52]. Furthermore, a closer investigation revealed that the deviations are attributed to cases in which the ground floor was below street level (for buildings with semi-basements), or to cases in which the first floor is above the street level (for buildings with pilotis).…”
Section: Codesupporting
confidence: 66%
See 1 more Smart Citation
“…In the other cases, there was a difference of 1 floor. This is acceptable and comparable with other open-source tools that achieve an error of 1 floor in building heights, which is sufficient for most city-scale analysis [52]. Furthermore, a closer investigation revealed that the deviations are attributed to cases in which the ground floor was below street level (for buildings with semi-basements), or to cases in which the first floor is above the street level (for buildings with pilotis).…”
Section: Codesupporting
confidence: 66%
“…In addition, the DTM models may not provide accurate information about the terrain, as sometimes, a building may have a semi-basement floor that is constructed below ground level (or constructed above ground level when the building has pilotis). Nevertheless, the number of floors were accurately estimated for the majority of the buildings in the case study (57%), and for the rest with accuracy of ±1 floors, which is considered acceptable for a large-scale analysis [52]. The building height and the number of floors can also be determined using other methods, including light detection and ranging data with high resolution [59].…”
Section: Building Characteristics and Ground Covermentioning
confidence: 90%